Innovation Strategies Among Medium and Large Enterprises in Dumaguete City, Negros Oriental - Merto, Anna Carla; Ybañez, Romario (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the ever-changing domain of innovation strategies and obstacles encountered by medium and large enterprises in Dumaguete City, Negros Oriental. Additionally, it put forth practical suggestions for higher education institutions (HEIs) to better align graduate education with the market's requirements. Surveys and interviews were used to meticulously collect data from 150 establishments using a comprehensive mixed-methods approach. Important insights were extracted through statistical analyses, such as frequency distribution and Pearson's correlation coefficient. The results indicated that the business environment was complex and varied, with organizations placing a high value on technological progress and product innovation while facing significant obstacles, including employee opposition, insufficient support from leadership, competitive forces, and regulatory intricacies. In order to tackle these challenges, the study proposed the implementation of capacity-building initiatives for decision- makers, targeted innovation support, the promotion of synergistic collaborations between academia and industry, and advocacy for policy frameworks that are conducive to progress. A comprehensive remedial strategy outlines pragmatic measures that local enterprises can undertake to strengthen their innovative capabilities; it emphasizes collaborative support networks, advocacy endeavors, and robust monitoring systems. This study made a substantial scholarly contribution to innovation management and business strategies, with significant implications for economic progress and the improvement of graduate education. When viewed through the lens of NOCCI, innovation becomes a critical factor in promoting entrepreneurial development and stimulating economic vitality in Negros Oriental. The proactive efforts undertaken by NOCCI to foster an innovative ecosystem via service provision, investment facilitation, collaborative ventures, and advocacy campaigns underscore the organization's dedication to promoting sustainable business growth and prosperity within the local community.